2019
DOI: 10.5811/westjem.2019.5.42762
|View full text |Cite
|
Sign up to set email alerts
|

Transportation Preferences of Patients Discharged from the Emergency Department in the Era of Ridesharing Apps

Abstract: Patients discharged from the emergency department (ED) may encounter difficulty finding transportation home, increasing length of stay and ED crowding. We sought to determine the preferences of patients discharged from the ED with regard to their transportation home, and their awareness and past use of ridesharing services such as Lyft and Uber. Methods: We performed a prospective, survey-based study during a five-month period at a universityassociated ED and Level I trauma center serving an urban area. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In veterans and civilians with established PTSD, it has been shown to reduce PTSD and associated symptoms 30–33 . Approximately 79% of ED patients in Level I trauma centers own smartphones 34 . Given this increased access, and that Hispanic and black individuals are more likely to rely on their mobile phone (vs. other devices) to access the Internet and health‐related information (see Anderson‐Lewis et al 35 ), PTSD Coach may present a unique opportunity to engage minority populations in mental health care and provide accessible and sustainable mental health care to underserved populations; 36 however, few evidence‐based digital tools are designed to prevent postinjury PTSD 27 (for exception, see Mouthaan et al 37 ), and no prior study has tested a PTSD‐focused self‐management mHealth app for ED patients with minor injuries.…”
mentioning
confidence: 99%
“…In veterans and civilians with established PTSD, it has been shown to reduce PTSD and associated symptoms 30–33 . Approximately 79% of ED patients in Level I trauma centers own smartphones 34 . Given this increased access, and that Hispanic and black individuals are more likely to rely on their mobile phone (vs. other devices) to access the Internet and health‐related information (see Anderson‐Lewis et al 35 ), PTSD Coach may present a unique opportunity to engage minority populations in mental health care and provide accessible and sustainable mental health care to underserved populations; 36 however, few evidence‐based digital tools are designed to prevent postinjury PTSD 27 (for exception, see Mouthaan et al 37 ), and no prior study has tested a PTSD‐focused self‐management mHealth app for ED patients with minor injuries.…”
mentioning
confidence: 99%
“…15,16 These ridesharing services have also piqued the interest of hospital systems aiming to provide non-emergency medical transportation services to their patients. [17][18][19] These efforts are bolstered by studies in primary care demonstrating improved show-rates when using ridesharing services, although other studies have not definitively demonstrated benefits in decreasing no-show rates. 22,23 Despite the broad availability of ridesharing services and their increasing utilization by hospital systems, there are no studies on the use of taxi services and limited research on the effect of ridesharing on ED LOS after discharge or interfacility transport.…”
Section: Discussionmentioning
confidence: 99%
“…A lower score could lead to alerting the discharge team, which can then put in place an appropriate package of care to facilitate safe and direct discharge from the ED. At the hospital, some patients were unable to exit the ED upon discharge due to lack of transportation, a problem that has been reported through other studies as well [53,118]. As a result, patients ended up boarding while ED staff had to spend time arranging for transport.…”
Section: Developing An Informed Alert System To Alleviate Waiting Tim...mentioning
confidence: 95%
“…For instance, specialist consultation, necessary to process complex patients, is a common throughputrelated bottleneck [50,52]. An output-specific bottleneck might be discharged patients who are unable to egress the ED due to the non-availability of transportation [53].…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation